Pengaruh Parameter Shot Terhadap Kekerasan dan Kekasaran Permukaan Melalui Proses Shot-Peening Stainless Steel Tipe 316 - M I Mukhsen; R Nur; C. R. Rakka; M. A. Fattah (Jurnal Teknik Mesin Sinergi, 2021)
Type 316 stainless steel is a material that is often used in the medical world, especially as a material for making bone implant plates. However, the use of stainless steel as an implant material, stainless steel must be treated to increase the hardness and adjust the level of roughness on the surface. In this study, shot peening was carried out on the 316 stainless steel surface. The shooting parameters used were 2, 4, 6 minutes for the shooting duration, and 0o, 15o, 30o, 45o for the shooting angle, as well as the diameter of the steel shot used, i.e. 0.6 mm and 1 mm. The results of this study indicated that there was a change in the characteristic properties of 316 stainless steel, namely the hardness and surface roughness.